Sense of Coherence and Stress-Related Resilience: Investigating the Mediating and Moderating Mechanisms in the Development of Resilience Following Stress or Adversity - Mc Gee, Shauna L.; Höltge, Jan; Maercker, Andreas; Thoma, Myriam V. (Frontiers in Psychiatry, 2018)
Background: Trauma, stress, and adversity are well-known for having lasting negative effects on health. Yet, not all individuals go on to develop psychopathology or impaired health. However, little is known about the underlying mechanisms which influence the development of stress-related resilience. Sense of coherence-revised (SOC-R) may play a role in this process, as it is formed through overcoming stress or adversity. It may also influence the steeling effect, which suggests that previous exposure to moderate adversity increases resilience to later adversities. Objectives: This study aimed to examine the mediating and moderating roles of SOC-R in the relationship between stress or adversity, and psychological health and well-being. It further aimed to investigate the role of SOC-R in steeling processes. Methods: The study used a longitudinal design, with data collection at baseline and one-year follow-up. Participants included (N=238) Swiss older adults (Mage=68.3 years). Standardised questionnaires assessed early-life adversity, recent chronic stress, SOC-R, and current health and well-being. Mediation and moderation analyses examined the mechanisms underpinning stress-related resilience and curvilinear associations assessed steeling. Results: Results showed that the Manageability subscale of SOC-R significantly moderated the relationship between chronic stress and general mental health (b = .04, 95% CI [.007, .082], t = 2.32, p<.05). Furthermore, SOC-R significantly mediated the relationship for general mental health (GMH) and satisfaction with life (SWL) with childhood emotional neglect (GMH: b = −.056, 95% BCa CI [−.126, −.002]; SWL: b = −.043, 95% BCa CI [−.088, −.004]), childhood physical neglect (GMH: b = −.100, 95% BCa CI [−.232, −.002]; SWL: b = −.081, 95% BCa CI [−.181, −.002]), and chronic stress (GMH: b = −.052, 95% BCa CI [−.100, −.001]; SWL: b = −.055, 95% BCa CI [−.097, −.020]). No curvilinear associations were observed between stress or adversity and SOC-R. Conclusions: This study expands on the limited research on stress-related resilience by examining the role of SOC-R in the interactions between adversity, stress, and health. Future research should examine SOC-R in samples with a greater range and different types of adversity. Overall, findings suggest that SOC-R is an important mechanism underpinning the development of stress-related resilience.